Beyond Glycemic Control: The Expanding Role of GLP-1 Analogues in Type 2 Diabetes and Metabolic Health - Michał Mazur; Dorota Waz; Jakub Szarłowicz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski; Sebastian Samuła (Quality in Sport)
Introduction and Purpose: